Morphological evolution in melanoma in situ using revised pattern analysis. (14th September 2020) - Ramji, Rajan; Oakley, Amanda; Rademaker, Marius
Abstract: Sequential digital dermoscopic imaging (SDDI) compares surface microscopy images of skin lesions over multiple time points. We utilized a retrospective SDDI cohort to investigate the development of dermoscopic features associated with malignancy in melanoma in situ (MIS). A total of 124 in situ melanomas were assessed from 110 Caucasian patients aged ≥18 years, with ≥2 serial images obtained between 1999 and 2017 and followed for a mean 41 months (3–142). As a positive control group, 58 invasive melanomas from 53 patients were also reviewed. Change in MIS size or number of colours correlated to time (both p  < .001). The odds of MIS displaying ≥3 clues to malignancy also correlated to time (OR 5.6–52.1) ( p  < .05). 75% of in situ melanomas matched a dermoscopic subtype on final imaging. While a clinically significant minority of in situ melanomas were unchanged or lost dermoscopic features, lesions predominantly increased in morphological complexity over time. Longer follow‐up periods allow dermoscopic features associated with malignancy and histopathological progression to develop.